Drought Detection and Solutions - Ondrasek, Gabrijel (IntechOpen, 2020)
Drought (hydrological, meteorological, and/or agronomical) disturbs water balance in certain domains and limits green/blue water resources for our basic needs, including food and energy production. This book presents the most recent insights related to drought types, their detection, and their effects on food, energy, and municipal water supplies. It also examines some novel approaches to drought management.